Analytical Study Of The Impact Of Syrian Imports On The National Economy During The Period (1995-2017) - Alrifai, Abdul Hadi; Ismail, Issam; Ayed, Mohamad (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research deals with the impact of the qualitative structure of imports on the economic growth in Syria during the period (1995-2017). Its role as one of the important factors affecting the economic growth rate in Syria during the period (1995-2017), thus trying to achieve the greatest possible benefit from imports in securing the needs and requirements of economic development and reconstruction. One of the most significant results reached is that Syrian imports of raw materials and intermediate goods ranked the most important imports in GDP before the war on Syria, while imports of manufactured materials and intermediate goods were the most influential in GDP during the war on Syria. تناولت هذه الدراسة أثر الهيكل النوعي للواردات في النمو الاقتصادي في سورية خلال الفترة (1995-2017), وذلك بالاعتماد على الناتج المحلي الإجمالي كمؤشر لقياس النمو الاقتصادي, وهدفت إلى تسليط الضوء على واقع الواردات السورية وتحليل هيكليتها قبل وخلال فترة الحرب على سورية, وإبراز دورها كأحد العوامل الهامة والمؤثرة في معدل النمو الاقتصادي في سورية خلال الفترة (1995-2017), وبالتالي محاولة تحقيق أكبر استفادة ممكنة من الواردات في تأمين احتياجات ومتطلبات عمليات التنمية الاقتصادية وإعادة الإعمار. ومن أبرز النتائج التي تم الوصول إليها أنّ الواردات السورية من المواد الخام ومن السلع الوسيطة احتلتا مرتبة الواردات الأكثر تأثيراً في الناتج المحلي الإجمالي قبل الحرب على سورية, في حين كانت الواردات من المواد المصنّعة والسلع الوسيطة هي الأكثر تأثيراً في الناتج المحلي الإجمالي خلال فترة الحرب على سورية.